Bacterial Dynamics of Wheat Silage - Keshri, Jitendra; Chen, Yaira; Pinto, Riky; Kroupitski, Yulia; Weinberg, Zwi G.; Sela Saldinger, Shlomo (Frontiers in Microbiology, 2019)
Knowledge regarding bacterial dynamics during crop ensiling is important for understanding of the fermentation process and may facilitate the production of nutritious and stable silage. The objective of this study was to analyze the bacterial dynamics associated with whole crop wheat silage with and without inoculants. Whole crop wheat was ensiled in laboratory silos, with and without Lactobacillus inoculants (L. plantarum, L. buchneri), for 3 months. Untreated and L. plantarum-treated silages were sampled at several times during ensiling, while L. buchneri-treated silage was sampled only at 3 months. Bacterial composition was studied using next generation sequencing approach. Dominant bacteria, before ensiling, were Pantoea (34.7%), Weissella (28.4%) and Pseudomonas (10.4%), Exiguobacterium (7.8%), and Paenibacillus (3.4%). Exogenous inoculants significantly affected bacterial composition and dynamics during ensiling. At 3 months of ensiling, Lactobacillus dominated the silage bacterial population and reached an abundance of 59.5%, 92.5%, and 98.2% in untreated, L. plantarum- and L. buchneri-treated silages, respectively. The bacterial diversity of the mature silage was lower in both treated silages compared to untreated silage. Functional profiling of the bacterial communities associated with the wheat ensiling demonstrated that the abundant pathways of membrane transporters, carbohydrate and amino acids metabolisms followed different pattern of relative abundance in untreated and L. plantarum-treated silages. Only 3 pathways, namely base-excision repair, pyruvate metabolism and transcription machinery, were significantly different between untreated and L. buchneri-treated silages upon maturation. Lactic acid content was higher in L. plantarum-treated silage compared to untreated and L. buchneri-treated silage. Still, the pH of both treated silages was lower in the two Lactobacillus-treated silages compared to untreated silage. Aerobic stability test demonstrated that L. plantarum-, but not L. buchneri-supplement, facilitated silage deterioration. The lower aerobic stability of the L. plantarum-treated silage may be attributed to lower content of acetic acid and other volatile fatty acids which inhibit aerobic yeasts and molds. Indeed, high yeast count was recorded, following exposure to air, only in L. plantarum-treated silage, supporting this notion. Analysis of bacterial community of crop silage can be used for optimization of the ensiling process and the selection of appropriate inoculants for improving aerobic stability.